KEEFEKTIFAN PROBLEM POSING DITINJAU DARI KEMAMPUAN MEMECAHKAN MASALAH MATEMATIS DAN KREATIVITAS SISWA SD NEGERI 26 KAYU PASAK KECAMATAN PALEMBAYAN KABUPATEN AGAM - Novia Rita; Desyandri (STKIP Subang, 2022)
The Effectiveness of Problem Posing Judging from the Ability to Solve Mathematical Problems and the Creativity of SD Negeri 26 Kayu Pasak Students, Palembayan District, Agam Regency. This study aims to analyze the effectiveness of problem posing learning in learning mathematics in terms of the ability to solve problems and the creativity of SD Negeri 26 Kayu Pasak students, Palembayan District, Agam Regency for the 2022/2023 academic year. This type of research is quasi-experimental research using pre-test and post-test designs with non-equivalent groups. The population in this study were all students of SD IV Negeri 26 Kayu Pasak, District of Palembayan, Regency of Agam and the samples were students of Class IV-A SD Negeri 26 Kayu Pasak, District of Palembayan, Agam Regency and students of Class IV-B SD Negeri 26 Kayu Pasak, District of Palembayan, Agam Regency who were selected using a purposive sampling technique. The data collection technique in this study used test techniques to measure problem-solving skills and creativity in the form of descriptive tests. Data analysis techniques using multivariate analysis of variance. The results of the Hotelling Trace (T2) test show that there are differences in the effectiveness of problem posing learning with conventional learning in terms of Problem Solving abilities and students' mathematical creativity. The results of the t-test show that for the problem-solving aspect of learning mathematics, problem-posing is not more effective than conventional learning, but in terms of creativity, problem-posing is more effective. So it can be concluded that the problem posing learning approach is more effective than conventional learning in terms of mathematical creativity in students at SD Negeri 26 Kayu Pasak, Palembayan District, Agam Regency in 2022/20